The Effect of Progressive Muscle Relaxation Using Audio-Visual Media on Blood Pressure Reduction in Elderly Hypertension Patients - Jajuk Kusumawaty (International Journal of Nursing and Health Services (IJNHS), 2021)
Introduction: Hypertension is one of the deadliest diseases in the world. Progressive muscle relaxation is one way of lowering blood pressure; this technique can control tension and anxiety by training patients to relax their body muscles deliberately. Choosing videos as a medium for health education is very suitable because the public can well receive them. This media offers an education that is more interesting and less monotonous. Objective: The study aimed to determine the effect of progressive muscle relaxation on blood pressure reduction in older adults with hypertension using audio-visual media. Method: This study used a pre-experimental method with one group pretest-posttest design. A total sample of 24 respondents was recruited using the purposive sampling technique. Result: The results found that the systolic blood pressure (p<0.001) and diastolic blood pressure (p<0.05) were significantly different before and after receiving the intervention. Conclusion. The progressive muscle relaxation affects blood pressure reduction in older people with hypertension with audio-visual media in the urban village linggarsari. Recommendation: Further studies are expected to be used as the basis for further research on the Effect of Progressive Muscle Relaxation with a combination of music or guided imagery on Blood Pressure Reduction. Clinical practice is expected to be used as a reference for more effective treatment of hypertension.